SenMoR-VR: A Sensory and Motoric Improving Function Tool for Children Development - Rinna Dwi Lestari; Penggalih M Herlambang; Muhammad Junaedi; Rani Tiyas Budiyanti (Journal of INISTA, 2022)
Many children have delayed development related to sensory and motoric function. Virtual reality can be developed to stimulate activity to develop the sensory and motoric function and adjust the physiotherapy. It can be more efficient, effective, and interactive, especially in the Z generation that is familiar with the technology. The study aims to develop and evaluate the SenMor-VR, virtual reality as a sensory and motoric improving function tool. The research method was research and development (R&D), which was initiated with situation analysis using literature review, development of the product, and evaluation This VR software contains many features i.e front-page, interactive games, and environments, and evaluation. Based on the technology acceptance model (TAM), the total average from the aspect of benefit of use is 4.5 which shows most of the respondents agree that this technology has benefits for them. The aspect of ease of use is 3.9 which shows that most of the respondents agree that this technology was easy to use. This virtual reality app has potency as a sensory and motoric improving function tool, but it needs further clinical research to evaluate its implementation in children.